Oral Health Effects of Combusted and Smokeless Tobacco Products. (October 2019) - Tomar, S.L.; Hecht, S.S.; Jaspers, I.; Gregory, R.L.; Stepanov, I.
The oral cavity is usually the first part of a consumer's body exposed to the constituents of tobacco products or their emissions. Consequently, the oral cavity is a frequent site for carcinogenic, microbial, immunologic, and clinical effects of tobacco use. This article summarizes 5 presentations on various aspects of oral health affected by combusted or noncombusted tobacco products from a recent conference, "Oral Health Effects of Tobacco Products: Science and Regulatory Policy, " sponsored by the American Association for Dental Research and the Food and Drug Administration.